The Ataxin-2 protein is required for microRNA function and synapse-specific long-term olfactory habituation. - McCann, C.; Holohan, E.E.; Das, S.; Dervan, A.; Larkin, A.; Lee, J.A.; Rodrigues, V.; Parker, R.; Ramaswami, M. (Proceedings of the National Academy of Sciences of the United States of America, 2011)
Local control of mRNA translation has been proposed as a mechanism for regulating synapse-specific plasticity associated with long-term memory. We show here that glomerulus-selective plasticity of Drosophila multiglomerular local interneurons observed during long-term olfactory habituation (LTH) requires the Ataxin-2 protein (Atx2) to function in uniglomerular projection neurons (PNs) postsynaptic to local interneurons (LNs). PN-selective knockdown of Atx2 selectively blocks LTH to odorants to which the PN responds and in addition selectively blocks LTH-associated structural and functional plasticity in odorant-responsive glomeruli. Atx2 has been shown previously to bind DEAD box helicases of the Me31B family, proteins associated with Argonaute (Ago) and microRNA (miRNA) function. Robust transdominant interactions of atx2 with me31B and ago1 indicate that Atx2 functions with miRNA-pathway components for LTH and associated synaptic plasticity. Further direct experiments show that Atx2 is required for miRNA-mediated repression of several translational reporters in vivo. Together, these observations (i) show that Atx2 and miRNA components regulate synapse-specific long-term plasticity in vivo; (ii) identify Atx2 as a component of the miRNA pathway; and (iii) provide insight into the biological function of Atx2 that is of potential relevance to spinocerebellar ataxia and neurodegenerative disease.